Beveridge Report (Pictorial charts with explanatory notes) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations Chart 3. COMPARATIVE COST OF SECURITY. 9. Average Expenditure on security made by male industrial workers at present 1937/38 Pence per week. For Adult Man Per Adult Man at 25% increase Insurance premiums, payments to pension funds, etc. 21.88 27.35 Medical treatment, including hospital, doctor, dentist, optician, midwife, nursing, drugs and appliances 15.36 19.20 Compulsory insurance 19.00 23.75 Total 56.24 70 30 (Beveridge Report. Table XV.) Beveridge plan contributions. Male Female Insured Person Employers Joint Insured Person Employers Joint Class I (Employees) Age 21 and upwards 4/3 3/3 7/6 3/6 2/6 6/- 18-20 3/6 2/9 6/3 3/- 2/- 5/- 16-17 2/6 2/6 5/- 2/- 2/- 4/- Class II (working on own account) Age 21 and upwards 4/3 - - 3/9 - - 18-20 3/6 - - 3/- - - 16-17 2/- - - 2/- - - Class IV (others of working age) Age 21 and upwards 3/9 - - 3/- - - 18-20 3/- - - 2/6 - - 16-17 1/6 - - 1/6 - - (Beveridge Report. para. 403.) Chart 4. OLD AGE PENSIONS. Estimated population of Great Britain by Age Groups 1901 to 1971 Year Total Under Per cent. of Men 65 and over Per cent. of Population 15 Total Women 60 and over Total 1901 36,999,946 12,040,841 32.5 2,284,481 6.2 1911 40,831,396 12,587,504 30.8 2,748,416 6.7 1921 42,769,196 11,940,167 27.9 3,349,222 7.8 1931 44,795,357 10,825,072 24.2 4,295,430 9.6 1943* 46,565,000 9,573,000 20.6 5,571,000 12.0 1951* 47,501,000 9,054,000 19.1 6,899,000 14.5 1961* 47,192,000 8,433,000 17.9 8,049,000 17.1 1971* 45,980,000 7,600,000 16.5 9,576,000 20.8 * Estimates based on White Paper on "Current Trend of Population in Great Britain." 126/TG/377/1/1/153